The Role of Parents' Religiosity in Raising Children and Its relationship to Child Behavior - an Educational Study from an Islamic Perspective - Ahmed Mahmood Saydok; Nazanin Muhialdin Maaroof (Zanco Journal of Humanity Sciences)
Islam directs parents to show high morals and be treated with mercy. So that their children grow up on integrity and independence of personality; therefore, the researchers tried to highlight the importance of the role of parents' religiosity in raising children and its relationship to the child's behavior. The research aims to: highlight the impact of religiosity on the educational process, and the most important religious educational methods on which the Islamic law relie. The research is divided into an introduction, two sections, and sources. The first section included two requirements: the first is concerned with defining the words of the study, and the second is related to religiosity and its relationship to human behavior. The second section includes two requirements as well. The first includes religious methods that affect verbal behavior, while the second requirement includes methods that affect practical behavior